Inbreeding in natural mammal populations: historical perspectives and future challenges. (5th September 2019) - Hasselgren, Malin; Norén, Karin
Abstract: The awareness of inbreeding as a potentially harmful process dates several centuries back in time, and occurred early in various religions, cultures, and societies. However, it was not until the 18th Century that the phenomenon was first investigated systematically through breeding experiments in domestic animals and plants. Investigations were followed by the establishment of the theoretical framework in the 19th Century by Darwin, Mendel and other pioneering evolutionary biologists. Throughout the development of this field, from breeding experiments and discoveries of the mechanism of inheritance, via heterozygosity‐fitness correlations, construction of pedigrees for natural populations, emergence of the conservation genetics field, to present‐day whole genome sequencing of extinct species, mammals have played a crucial role as model organisms and flagship species. In this review, we present a chronological overview of the theoretical development and empirical data on inbreeding in mammals, from the 18th Century to the present day. Furthermore, in relation to the current analytical capacity, we identify gaps in the knowledge and future challenges in the study of inbreeding and inbreeding depression in mammals.